Freshwater fungi in the karst plateau wetlands from Guizhou Province, China: taxonomic novelties in Melanommataceae (Pleosporales) - Ling-Ling Liu; Yong-Xiang Liu; Ya-Ya Chen; Jiu-Lan Gou; Feng Chi; Yi Liu; Xiao-Feng Gu; Quan-Quan Wei; Meng Zhang; Zuo-Yi Liu; Si Zhou (MycoKeys)
Three isolates of interest were collected during an investigation of freshwater fungi from wetlands in the karst regions of Guizhou Province, Southwest China. Phylogenetic analyses using ITS, LSU, SSU, and tef-1α gene regions have revealed the placements of these isolates in Melanommataceae (Pleosporales, Dothideomycetes). Based on the morphological and phylogenetic evidence, three new species are introduced: Byssosphaeria chishuiensis sp. nov., Camposporium guizhouense sp. nov., and C. aquaticum sp. nov. Byssosphaeria chishuiensis is sister to B. villosa and forms a basal branch of Byssosphaeria within Melanommataceae. Byssosphaeria chishuiense is similar to B. villosa in ascal size but differs in the ascomata and ascospore sizes, and the ascospores lack appendages. Camposporium aquaticum is sister to C. guizhouense, and they form a distinct lineage within the genus. Morphologically, C. aquaticum resembles C. guizhouense in its conidial shape but differs in conidial size. Additionally, PHI analysis is performed to further reveal that C. aquaticum and C. guizhouense have no significant recombination with related taxa. Neobyssosphaeria is synonymized under Byssosphaeria, and accordingly, Byssosphaeria clematidis comb. nov. is proposed to accommodate Neobyssosphaeria clematidis. The descriptions, illustrations, and notes of the novel taxa are provided along with an updated phylogenetic tree of Melanommataceae. Two synopses of the species in Byssosphaeria and Camposporium are also provided.